PENGARUH MOTIVASI, DISIPLIN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN DI PT. CSK INSULATION ENGINEERING KOTA BATAM - Prince Hartawan; Mauli Siagian (LPPM STIE Muhammadiah Bandung, 2026)
In today's business field, many companies have experienced significant changes in progress and development. This is what the company has been waiting for to achieve in its business. The development of the company's progress occured because of an increase in the potential of the company's human resources, so that it can be seen that human resources are a determinant of success or failure in a company. The research here aims to determine the influence of discipline, motivation and job training on employee performance. Researchers conducted research at PT. CSK Insulation Engineering Batam City with a quantitative-based research method in multiple linear analysis taken by sampling technique using Quota Sampling. In this study also took samples with non-probability sampling with a total sample of 120 people and resulted that can be implied that discipline, motivation and work training provide significant and positive results on employee performance at PT. CSK Insulation Engineering Batam City.